Firm performance and managerial turnover: the case of Ukraine - Alexander Muravyev; Oleksandr Talavera; Olga Bilyk; Bogdana Grechaniuk (Institute for the Study of Labor (IZA), 2009)
The paper studies whether and how CEO turnover in Ukrainian firms is related to their performance. Based on a novel dataset covering Ukrainian joint stock companies in 2002-2006, the paper finds statistically significant negative association between the past performance of firms measured by return on sales and return on assets, and the likelihood of managerial turnover. While the strength of the turnover-performance relationship does not seem to depend on factors such as managerial ownership and supervisory board size, we do find significant entrenchments effects associated with ownership by managers. Overall, our analysis suggests that corporate governance in Ukraine operates with a certain degree of efficiency, despite the well-known lacunas in the country's institutional environment.
Keywords: G34; J40; L29; 330; Managerial labor market; corporate governance; transition; Ukraine; Führungskräfte; Arbeitsmobilität; Kündigung; Unternehmensentwicklung; Corporate Governance; Ukraine